Pengaruh Inflasi Dan Bi Rate Terhadap Perubahan Laba Operasional Pada Bank Syariah - Nur Ahmadi Bi Rahmani (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study was conducted to find out the effect of inflation and the BI Rate on the operating profit of Islamic banks for the period 2017 2019. This research is sourced from the financial statements of Islamic banks and Islamic banking statistics through the official website. The analysis technique used includes multiple linear regression. Using SPSS 24 data processing tool. The results of this study indicate that partially inflation has a positive and significant effect on operating profit and the BI Rate partially has a positive and significant effect on operating profit. Simultaneously, Inflation and BI Rate affect the Operating Profit of Islamic Banks.